2015
DOI: 10.17812/blj2015.32.24
|View full text |Cite
|
Sign up to set email alerts
|

Growth response and antioxidant enzyme activity of Cassia occidentalis exposed to soil moisture stress

Abstract: Biotic and abiotic stresses exert a considerable influence on the growth and physiology of plants. Water stress is one of the most important abiotic stress factors. The study was carried out to elucidate the effect of drought stress on growth, physiology and antioxidant enzyme activity of Cassia occidentalis experiencing four water regimes with soil relative water content ranging from 65% to 12%. Plants were grown in pots and treated with three irrigation levels (100ml, 200ml and 300ml).The experiment was laid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…In this study we found a significant increase in EL percentage in all three species under both MWD and SWD treatments as compared to control conditions ( Figure 2). These results are consistent with the findings on Cassia occidentalis where a significant increase in EL percentage has been evidenced under water stress [49]. Furthermore, EL percentage was found the highest in Salix tetrasperma under SWD which shows a high membrane sensitivity of Salix tetrasperma to high water stress.…”
Section: Intraspecific Variability and Role Of Antioxidants In Stresssupporting
confidence: 92%
“…In this study we found a significant increase in EL percentage in all three species under both MWD and SWD treatments as compared to control conditions ( Figure 2). These results are consistent with the findings on Cassia occidentalis where a significant increase in EL percentage has been evidenced under water stress [49]. Furthermore, EL percentage was found the highest in Salix tetrasperma under SWD which shows a high membrane sensitivity of Salix tetrasperma to high water stress.…”
Section: Intraspecific Variability and Role Of Antioxidants In Stresssupporting
confidence: 92%
“…lanatus ). Furthermore, drought stress caused an increase in EL compared to well-watered conditions in Cassia occidentalis ( Srivastava and Srivastava, 2015 ). The drought tolerance in young oil palm plants was related to efficient protective mechanisms against ROS by activating enzymatic and non-enzymatic antioxidant strategies simultaneously ( Silva et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…To isolate these microbes with the ability to resist abiotic stress and able to remediate heavy metals, a good approach is to target the rhizospheric microbes of suffrutescent weed plants with these properties. Senna occidentalis is a pantropical medicinal weed that is resistant to drought, remediates heavy metals and is associated with plant growth-promoting bacteria [ 29 , 30 , 31 ]. Our aim was to isolate and characterize a Bacillus strain from Senna occidentalis to predict its applications in different biotechnological sectors.…”
Section: Introductionmentioning
confidence: 99%